La fase administrativa del trámite de adopción en el Código De La Niñez Y Adolescencia Del Ecuador - Bohorquez Litardo, Ronald Wladimir (2015)
This research work I have developed within the legal field, specifically on the shortcomings that exist in the Organic Code of Childhood and Adolescence, in what concerns the administrative procedure for the adoption to be a very lengthy process. At present, the adoption is primarily focused on children and adolescents deprived of their family environment; operating as a measure of protection provided by the state and society in favor of them. However, a number of laws do not limit the shape of the adoption of minors; so that Ecuadorian legislation through Article 165 and following of the Code of Childhood and Adolescence establishes an adoption process unregulated or establish specific periods during the administrative procedure. What the present investigation seeks to determine is the purpose of adoption with certain time and not the problem currently generates, in which the process turns into chaotic and lengthy paperwork that makes adoption under state are unprotected and stability families legally grant them protection and economic and emotional than the natural family could not give it stability. The problem generated is that abandoned children find a real family for the administrative procedures are too long, so cause legal uncertainty adopted and adopters. Therefore we say that adoption is not an option but a vocation and that is to start a family with the child or adolescent who is in the possibility of being adopted, thus forming the new family will have the security and state guarantee because it has an obligation to protect the core of the society